A STUDY ON SUPERVISED LEARNING MODEL – K-NN CLASSIFICATION (International Journal of Food and Nutritional Sciences, 2022)
In the world of machine learning, the k-Nearest Neighbors (kNN) algorithm has emerged as apowerful tool for classification tasks. With its simplicity and effectiveness, kNN has gainedpopularity across various domains. In this article, we will explore the fundamentals of kNN,its applications, and implementation. Whether you are a beginner or an experiencedpractitioner in machine learning, this article will provide valuable insights into thecapabilities of kNN and how it can be leveraged to make accurate predictions. So, let's diveinto the world of k-Nearest Neighbors and unlock its potential!